Implementation of the Principal's Managerial Function in Improving the Quality of Education Based on Education Report Achievements - Dina Hikmah Safariyah; Senowarsito; Maryanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe the role of the principal in improving academic quality through managerial functions at SDN 02 Bumirejo. The background of the study is based on the importance of principal leadership in optimizing educational resources to achieve quality academic outcomes. The study used a qualitative approach with a descriptive type. Research subjects were selected by purposive sampling which included the principal, teachers, education staff, and the school committee. Data were obtained through interviews, observations, and documentation, then analyzed through the stages of reduction, presentation, and drawing conclusions with validity tests using technical triangulation. The results of the study indicate that the principal carries out four managerial functions in an integrated manner, namely planning, organizing, directing, and evaluating. Program planning is carried out in a participatory manner and based on Education Report Card data. Organization is carried out with the principle of suitability of tasks and competencies and optimization of infrastructure. Direction is carried out with an instructive and motivational approach through open communication and continuous professional development. Evaluation is carried out routinely through supervision, providing feedback, and concrete follow-up. All of these functions impact teacher competency, create a conducive work climate, and improve student literacy and numeracy outcomes. Thus, this study confirms that effective principal leadership contributes significantly to improving the academic quality of elementary schools.